The Imagination in Silence - a Discussion about Sylvia Plath's The Wishing Box - Da Rocha, Guilherme Magri [UNESP]; Rapucci, Cleide Antonia [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2019)
In agreement with Lissa Paul (1997), we understand that one of the purposes of feminist criticism is to present re-readings and revisions of texts considered of less importance within the work of a certain writer. Therefore, this paper aims to problematize issues related to the literature of female authorship through a reading of The Wishing Box, a short-story written by Sylvia Plath (1932-1963), which was compiled by Ted Hughes (1930-1998) in the collection Johnny Panic and the Bible of Dreams (1977). In order to achieve this objective, we seek to examine, in the aforementioned short-story, the protagonist's representation, discussing gender relations as a category of analysis. This article is justified considering that there are few academic works involving Plath's short fiction, more specifically, in studies on female authorship writing.
Keywords: American Literature; Gender; Representation; Sylvia Plath; Women Writers